Social studies today research and practice - Parker, Walter C. (New York,NY Routledge, 2015)
Written by the field's leading scholars, this collection provokes readers to consider the relationship of research and practice as they think through some of the most interesting challenges that animate social studies education today.
Social studies education eC21 / Walter C. Parker -- Social studies and the social order : transmission or transformation? / William B. Stanley -- The social studies wars, now and then / Ronald W. Evans -- Why don't more history teachers engage students in interpretation? / Keith C. Barton and Linda S. Levstik -- High-stakes testing : how are social studies teachers responding? / S.G. Grant -- Authentic intellectual work : common standards for teaching social studies / M. Bruce King, Fred M. Newmann, and Dana L. Carmichael -- Education and diversity / James A. Banks ... [et al.] -- Isn't culturally responsive instruction just good teaching? / Kathryn H. Au -- Silence on gays and lesbians in social studies curriculum / Stephen J. Thornton -- Race, gender, and the teaching and learning of national history / Terrie Epstein and Jessica Shiller -- What can Forrest Gump tell us about students' historical understanding? / Sam Wineburg, Susan Mosborg, and Dan Porat -- What does it mean to think historically ... and how do you teach it? / Bruce A. Vansledright -- Maps and map learning in social studies / Sarah Witham Bednarz, Gillian Acheson, and Robert S. Bednarz -- What do children know about cultural universals? / Jere Brophy and Janet Alleman -- High quality civic education : what is it and who gets it? / Joseph Kahne and Ellen Middaugh -- Holocaust fatigue in teaching today / Simone Schweber -- How are teachers responding to globalization? / Merry M. Merryfield and Masataka Kasai -- Using literature to teach about others : the case of Shabanu / Margaret Smith Crocco -- The two world histories / Ross E. Dunn -- Teaching civic engagement in five societies / Carole L. Hahn -- Discussion in social studies : is it worth the trouble? / Diana E. Hess -- What constrains meaningful social studies teaching? / Catherine Cornbleth -- What is the connection between curriculum and instruction? / Avner Segall -- Can tolerance be taught? / Patricia G. Avery -- Idiocy, puberty, and citizenship : the road ahead / Walter C. Parker.
Includes bibliographical references and index.
Keywords: Social sciences -- Study and teaching (Secondary); Social sciences -- Study and teaching (Middle school)